Implementasi Model Evaluasi APKG dalam Penyusunan Modul Ajar Bahasa Indonesia: Studi Pada Materi Teks Ilmiah Populer - Farahdila, Nonika; Wagiran, Wagiran (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
This study raises the issue of the suboptimal preparation of learning modules that support the learning of popular scientific texts to improve students' literacy and critical thinking skills. The underlying theory is the APKG-1 (Teacher Competency Assessment Tool)-based learning evaluation approach, which assesses various aspects of learning planning. The research method used is qualitative evaluative, through learning modules, interviews with teachers, and library sources and scientific articles. The analysis process includes evaluating the learning module using APKG-1, calculating the average score, categorizing the results in an assessment scale, and analyzing, comparing, and evaluating the results. The results of the study indicate that determining the learning topics and formulating learning objectives in the learning module are very good (score 85). However, aspects of developing materials, media, and learning resources still need to be improved (score 69). Meanwhile, planning learning scenarios (score 83), classroom management (score 77.5), assessment planning (score 72.5), and display of planning documents (score 84.5) are in the good category. The conclusion is that the implementation of APKG-1 can help evaluate and improve the quality of teaching modules that support more effective learning.